RANCANG BANGUN PENGENDALI MOTOR STEPPER UNTUK DETEKSI JUMLAH OBYEK PUTAR DENGAN MENGGUNAKAN KOMPUTER - Sumariyah, Sumariyah; Sudarmanto, Agus; Gunadi, Isnain (BERKALA FISIKA, 2011)
It has been designed a mechanical equipment what could moving rotate each 45Â° and moving up and down betake to sensor hole, that be drive by two stepper motors. The operation of both stepper motors use Turbo Pascal language programming 5.5 version. The mechanical equipment could be operated in a automatically that is for moved the object rotate each 45Â° then the object betake down aim sensor hole and execute detection the object so after detected then the object move ascend aim first position. Result of using this mechanical equipment was have appearing result from detection object be automatically that is amounting to eight objects. Â Keyword : PC, stepper motors, object rotate.